Implementasi Kebijakan Otoritas Jasa Keuangan Mendukung Pemulihan Ekonomi dan Minat Pasar Modal - Erlina, Erlina; Mahfudh, Afif (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2026)
ABSTRACTThe Covid-19 pandemic placed significant pressure on Indonesia’s capital market, prompting the government, within the existing legal framework, to adopt strategic policies to maintain stability, restore investor confidence, and increase public participation. This study aims to analyze the implementation of Financial Services Authority policies in supporting national economic recovery and to examine factors driving the rise in investors during the pandemic. This research employs a normative juridical method with a statutory approach and qualitative descriptive analysis. The results show that policies implemented by the Financial Services Authority and Self-Regulatory Organizations effectively maintained market stability and supported economic recovery. The increase in investors was driven by adaptive policies, accelerated digitalization, and internal and external factors, strengthening the capital market’s role in economic recovery.Keywords: Implementation; Financial Services Authority; Capital Markets.ABSTRAKPandemi Covid-19 menyebabkan pelemahan signifikan pasar modal Indonesia yang mendorong pemerintah, melalui dasar hukum yang ada, untuk menetapkan kebijakan strategis guna menjaga stabilitas, memulihkan kepercayaan investor, dan meningkatkan partisipasi di pasar modal. Tujuan penelitian untuk mengetahui implementasi kebijakan Otoritas Jasa Keuangan dalam mendukung perekonomian akibat Covid-19 di Indonesia guna meningkatkan minat pasar modal dan mengapa terjadi peningkatan jumlah investor di pasar modal pada masa pandemi Covid-19. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa kebijakan Otoritas Jasa Keuangan bersama Self-Regulatory Organization efektif menjaga stabilitas pasar modal dan mendukung pemulihan ekonomi nasional. Peningkatan investor pasar modal didorong kebijakan, digitalisasi, dan faktor internal-eksternal, sehingga mendukung pemulihan ekonomi nasional.Kata Kunci: Implementasi; Otoritas Jasa Keuangan; Pasar Modal